1996
DOI: 10.1159/000139400
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Secretion in the Guinea Pig Duodenum: Functional Characterization of Peptide Hormone Receptors in Duodenal Enterocytes

Abstract: To get information about the peptide hormone receptors involved in duodenal bicarbonate secretion (DBS) and their cellular location, we determined DBS and adenylate cyclase (AC) activity in response to hormones of the vasoactive intestinal polypeptide (VΙP)/secretin family of peptides. DBS was determined in an isolated, perfused (24 mmol/l NaHCO3) loop of the proximal duodenum in urethane- and indometacin-treated guinea pigs. AC stimulation was measured in isolated, homogenized duodenal enterocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…VIP and PGE2 were shown to act via receptors coupled to adenylate cyclase in iso lated enterocytes in the rat [23] and man [24], We have recently reported that VIP and PGE2 potently stimulate adenylate cyclase and protein kinase A in homogenized duodenal enterocytes, but secretin and PGF2(1 were only weak stimulants [21], This is consistent with the strong effects of PGE2 and VIP on duodenal bicarbonate secre tion in this study. We have recently described the pres ence on duodenal enterocytes of VIP receptors [25] and EP2 subtype receptors for PGE2 [15], All this is corrobora tive evidence for the role of cAMP in bicarbonate secre tion.…”
Section: Second Messengers O F Bicarbonate Secretionsupporting
confidence: 60%
“…VIP and PGE2 were shown to act via receptors coupled to adenylate cyclase in iso lated enterocytes in the rat [23] and man [24], We have recently reported that VIP and PGE2 potently stimulate adenylate cyclase and protein kinase A in homogenized duodenal enterocytes, but secretin and PGF2(1 were only weak stimulants [21], This is consistent with the strong effects of PGE2 and VIP on duodenal bicarbonate secre tion in this study. We have recently described the pres ence on duodenal enterocytes of VIP receptors [25] and EP2 subtype receptors for PGE2 [15], All this is corrobora tive evidence for the role of cAMP in bicarbonate secre tion.…”
Section: Second Messengers O F Bicarbonate Secretionsupporting
confidence: 60%
“…VPAC 2 receptor mRNA has been identified in duodenal mucosa and epithelium [14]. Specific VIP receptors have been found on duodenocytes [41], and secretin does not stimulate these receptors. If, as indicated above, this VIP receptor is the VPAC 2 receptor, equal effects of PACAP27, PACAP38 and VIP on DMBS are to be expected.…”
Section: Discussionmentioning
confidence: 99%